PENGARUH PERSEPSI PENGETAHUAN PERATURAN PAJAK, SISTEM PERPAJAKAN, KESADARAN MEMBAYAR PAJAK DAN KONDISI KEUANGAN TERHADAP KEMAUAN MEMBAYAR PAJAK PENGHASILAN PADA WAJIB PAJAK - Ita Dewi Sulastri, Suharno & Fadjar Harimurti (Universitas Slamet Riyadi, 2016)
Purpose of this research to knows the effect of knowledge and understanding of taxpayers, perception of the taxation system, pay taxes awareness, financial condition on willingness to pay. This study is a survey of taxpayers with free work include lawyers, doctors, notaries and entrepreneurs in the district of Sragen Karangmalang which number as many as 264 taxpayers. A sample of 66 taxpayers. The data source used primary data and secondary data. Data collection techniques used questionnaires and literature Data was analyzed used multiple linear regression, F test, t test, the coefficient of determination. The survey results revealed that knowledge and understanding of taxpayers, perception of the taxation system, pay taxes awareness, financial condition has positive and significant effect on willingness to pay partialy and simultaneously.Keywords: knowledge and understanding of taxpayers, perception of the taxation system, pay taxes awareness, financial condition, willingness to pay